Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27528
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-Vortex Turbine Film Cooling Hole Concept

Abstract: A novel turbine film cooling hole shape has been conceived and designed at NASA Glenn Research Center. This “anti-vortex” design is unique in that it requires only easily machinable round holes, unlike shaped film cooling holes and other advanced concepts. The hole design is intended to counteract the detrimental vorticity associated with standard circular cross-section film cooling holes. This vorticity typically entrains hot freestream gas and is associated with jet separation from the turbine blade surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…Schulz et al [8] have done the experimental investigations of an anti-vortex film cooling geometry under low and high turbulence conditions. Similar observations have been reported as the previous results [6,7]. It is suggested that the new hole design reduces the jet exit momentum, preventing jet detachment leads to significant improvement in film cooling effectiveness.…”
Section: Literature Reviewsupporting
confidence: 80%
See 1 more Smart Citation
“…Schulz et al [8] have done the experimental investigations of an anti-vortex film cooling geometry under low and high turbulence conditions. Similar observations have been reported as the previous results [6,7]. It is suggested that the new hole design reduces the jet exit momentum, preventing jet detachment leads to significant improvement in film cooling effectiveness.…”
Section: Literature Reviewsupporting
confidence: 80%
“…However, among all the considered cases, shaped hole producing better-quality film cooling effectiveness mainly due to better coolant distribution in the lateral direction and at near the hole. Heidmann et al [6] have proposed new cooling hole design namely anti-vortex film cooling hole. The anti-vortex cooling hole consists of single hole which accompanied with two sister holes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The anti-vortex hole (AVH) geometry was developed by Heidmann et al [6] and could possibly, though optimization reduce or counter the vorticity of the counter rotating vortex that exists in conventional straight and even shaped hole film cooling schemes. The geometry examined in this study was selected from the study by Dhungel et al [7] that compared six different anti-vortex hole geometries.…”
Section: Film Cooling Geometrymentioning
confidence: 99%
“…The concept of Anti-Vortex Hole (AVH) was developed by Heidmann et al [6] in order to reduce this vortex effect by introducing two side holes that produce a strong upwash effect that is intended to balance the downwash on the outside of the main hole jet CRV or "kidney vortex". This is the main difference between the AVH and single hole geometry.…”
Section: Visualization Of Counter Rotating Vorticesmentioning
confidence: 99%
See 1 more Smart Citation